Relationship between Islamic Human Resources Management (IHRM) Practices and Organizational Justice: An Empirical Study - Hermanita Hermanita; Dimas Pratomo (Annals of Human Resource Management Research, 2026)
Purpose: This study analyzes the influence of Islamic Human Resource Management (IHRM) practices on Organizational Justice, with Islamic Remuneration and Compensation as a moderator. Research Methodology: A quantitative approach using primary survey data collected from employees of Islamic financial institutions in Indonesia was used. Hypotheses were tested using Structural Equation Modeling with Partial Least Squares (PLS-SEM). The measurement model confirmed the validity, reliability, and discriminant validity of all constructs, including factor loadings, composite reliability, and the Fornell-Larcker criterion. Results: Islamic Recruitment and Selection significantly and positively affected Organizational Justice. Islamic Training and Development had no significant direct effect. Islamic Remuneration and Compensation significantly affect Organizational Justice and successfully strengthen the positive relationship between Islamic Recruitment and Selection and Organizational Justice. The research model demonstrates strong explanatory power for the variance in Organizational Justice, with a substantial R-squared value. Conclusions: This study highlights the critical role of Islamic Recruitment and Selection and Islamic Remuneration in fostering a fair organizational climate. This emphasizes the necessity of an integrated IHRM system to improve perceptions of justice in Islamic financial institutions. Limitations: This study is limited by its focus on Islamic financial institutions in Indonesia, which may reduce generalizability. Additionally, the cross-sectional design and reliance on self-reported data may introduce biases. Contributions: This study contributes to the field of IHRM by integrating Islamic values with contemporary HR practices, offering practical insights into enhancing organizational justice in Islamic institutions, and providing a methodological framework for future research.